"The nightingale is a graceful dancer": Bulbul Chowdhury, dance heritage, and the new nation-state of Pakistan. Issue 4 (2nd October 2022) - Basu, Priyanka
ABSTRACT: This article focusses on the cultural work of dancer Bulbul Chowdhury who performed extensively in East and West Pakistan (1950) and toured Europe with his troupe (1953). Chowdhury's approach towards dance in newly formed Pakistan coincided with larger political events of WWII, Bengal Famine, Partition as well as the Language Movement. His methodology of dance encompassed a vision of "inter-Asia" in which he excavated Muslim pasts to create a vocabulary of "national dance" for Pakistan. During early years of decolonisation and Cold War, Chowdhury's performances for the Shah of Iran in Sylhet or for Jawaharlal Nehru following the Nehru-Liaquat Pact signified how such high-level state events were crucial for his travel abroad and thus gained a cultural currency/endorsement for his troupe. Drawing upon Kuan-Hsing Chen's "Asia as Method" (2010), this article concentrates on Chowdhury's role in connected geographies to identify structural limitations and alternative possibilities of knowledge production in dance.